Role of Inhaled Corticosteroid in Management of Episodic Viral Wheezing and Persistent Asthma in Pre-School Children–in A Peripheral Hospital, Bangladesh (Journal of Comilla Medical College Teachers' Association, 2025)
Background: Asthma is the most common chronic respiratory condition of childhood worldwide, characterized by recurrent cough and wheeze, with around 14% of children and young people affected. Viral wheezing is a common clinical condition during early childhood, approximately 50% of children experience at least one episode at preschool age. The article summarizes the inhaled corticosteroid treatment of childhood asthma and episodic viral wheeze, with an emphasis on new modalities.Methods: This retrospective study was conducted in combined military hospital, Sylhet. All members ages 2 to 6 years with an asthma and wheeze diagnosis during April 2021 to March 2022 and at least one hospital admission with more than one visit to child specialist were included. Asthma outcomes during the hospital admission and follow up visit were documented.Results: A total of 244 hospital admitted children were diagnosed with asthma and viral wheeze. Among them hospital admission was indicated 184 patients due to respiratory distress. The choice of treatment was inhaled corticosteroid along with antibiotics. Amoxicillin –clavulanate was the most prescribed antibiotics. The drugs dose, interval and route of administration were respected in all cases. Children treated with inhaled corticosteroid had significantly improve their symptoms and lung function. A substantial reduction in the prescription of corticosteroids was noted.Conclusion: We found significant positive outcomes after inhaled corticosteroid treatment in viral wheeze and childhood asthma. Referring paediatric asthma patients at right time at right place should be one of the goals of an asthma and viral wheezing management plan.J Com Med Col Teachers’ Asso July 2025; 29(2):98-102